KONSEP ETIKA DALAM DAKWAH - Fatihah, Siti Rohmatul (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2018)
Da'wah must be done with science. People who have an interest in plunging into the world of da'wah are required to understand the rules and mechanisms of dakwah fully intact before further practicing it. If one is forced to do da'wah without controlling or understanding knowledge (among other things related to ethics and aesthetics of da'wah), not only the process and the result is not good, but also the consequences can be dangerous, both for the image of Islam, da'wah, and religious life in general . Because, deeper and broader understanding and understanding of religious teachings, community life, and ways of preaching (including ethics and aesthetics), the dakwah is shown more wise, wise, touching, interesting, memorable, and longing. **** Dakwah harus dilakukan dengan ilmu. Orang yang memiliki minat terjun ke dunia dakwah di wajibkan memahami aturan-aturan dan mekanisme dakwah dengan utuh secara sempurna sebelum lebih jauh mempraktikkannya. Jika seseorang memaksakan diri melakukan dakwah tanpa menuguasai atau memahami ilmu (antara lain berkaitan dengan etika dan estetika dakwah), bukan hanya proses dan hasilnya yang kurang baik, tetapi juga akibatnya dapat menjadi berbahaya, baik bagi citra Islam, dakwah, maupun kehidupan keagamaan pada umumnya. Karena, semakin dalam dan luas pemahaman serta waawasan dai terhadap ajaran agama, kehidupan masyarakat, serta cara berdakwah (termasuk di dalamnya etika dan estetika), maka dakwah yang ditunjukkan semakin arif, bijak, menyentuh, menarik, mengesankan, dan dirindukan.